1997
DOI: 10.1007/s002239900371
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Microspectroscopic Analysis of Normal Human Cortical and Trabecular Bone

Abstract: Fourier transform infrared microspectroscopy (FTIRM) has been used to study the changes in mineral and matrix content and composition in replicate biopsies of nonosteoporotic human cortical and trabecular bone. Changes in osteonal bone in these same samples were reported previously. Spectral maps along and across the lamellae were obtained from iliac crest biopsies of two necropsy cases. Mineral:matrix ratios, calculated from the integrated areas of the phosphate nu1, nu3 band at 900-1200 cm-1 and the amide I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
167
2
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(182 citation statements)
references
References 25 publications
8
167
2
5
Order By: Relevance
“…Although carbonate incorporation has been reported to increase [64,75,76] and decrease [45,77] with age, no correlation with age was observed for the carbonate to phosphate ratio values in this study. This is consistent with [66], who found carbonate incorporation remained constant after 45 years old.…”
Section: Ftircontrasting
confidence: 87%
See 1 more Smart Citation
“…Although carbonate incorporation has been reported to increase [64,75,76] and decrease [45,77] with age, no correlation with age was observed for the carbonate to phosphate ratio values in this study. This is consistent with [66], who found carbonate incorporation remained constant after 45 years old.…”
Section: Ftircontrasting
confidence: 87%
“…When age matched, the mineral to organic ratio was not significantly different between the fracture and non-fracture group, although the values for the fracture group were lower. In contrast, previous studies have shown a decrease in the mineral to organic ratio in ovariectomized animal and osteoporotic human tissue [18,30,33,45,74], suggesting either a lower mineral content and/ or a greater collagen content. The consensus tends to be that in osteoporotic bone, a decrease in mineral content is observed [18,19], resulting in a reduction in mechanical strength [11].…”
Section: Ftircontrasting
confidence: 62%
“…[35][36][37][38][39][40] Briefly, a 4-mm-thick section was cut from each embedded bone sample and placed between two barium fluoride discs. Infrared spectra were collected from these sandwiched bone specimens using a microscope attached to a Nexus 670 FTIR spectrometer (Thermo Electron, Waltham, MA) operating in transmission mode for 200 scans at a 4-cm 21 resolution.…”
Section: Spectroscopic Assessment Of Bone Materialsmentioning
confidence: 99%
“…Crystallinity, a measurement of crystal size along the largest dimension, was calculated from the ratio of the areas under the peaks located at 1020 and 1030 cm 21 . 35,37,43 The relative amount of collagen crosslinking, also known as collagen maturation, was obtained by taking the ratio of the amount of mature enzymatic crosslinks (pyridinium) normalized by the amount of immature enzymatic crosslinks (reducible collagen crosslinks). Collagen crosslinking was calculated from the ratio of the areas under the peaks located at 1660 and 1690 cm 21 .…”
Section: Spectroscopic Assessment Of Bone Materialsmentioning
confidence: 99%
“…The utility of FTIR microspectroscopy in studying mineralized tissues is well established (33)(34)(35)(36). The technique combines histology-like spatial localization with the quantitative capability of bulk chemical analysis and it is used routinely in such specimens to assess the spatial distribution of mineral and collagen (from the phosphate and amide peaks, respectively) (37,38). It also provides information about mineral crystallinity as a function of spatial location in a sample such as the growth plate of a rat (39) or at distances from an osteon in human bone (40) or from the dentin-enamel junction in the human tooth (41).…”
Section: Introductionmentioning
confidence: 99%